MENGKOBINASIKAN GAMES DENGAN STRATEGI BUZZ GROUPS UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA PADA KELAS GRAMMAR - Dwi TM Wardhani (Relawan Jurnal Indonesia, 2018)
The final goal of this study is to know the effectiveness of learning methods that combine games with the Buzz Groups strategy to improve students' ability in Grammar classes at Faculty of letters at Abdurachman Saleh Situbondo University. Buzz Groups is a discussion group that discusses a topic and exchange ideas to solve a problem, where the same discussion method in each meeting will saturate students so that a combination of games is needed so the discussion is not boring. The combination of games and strategy was chosen because Grammar class is a subject that tends to be boring because the material is rather difficult for students, so it needs a way to keep them excited, happy and play an active role in learning activities. This study is a classroom action research that is made in one research cycle. The data in this study will be obtained during learning activities, where the existence of this research is expected to be able to assist teachers / lecturers in teaching English so that the methods used are more varied and the learning targets are expected to be achieved.